Expression of PDCD5, a novel apoptosis related protein, in human osteoarthritic cartilage - CHENG Ai-xin; LOU Si-quan; ZHOU Hao-wei; WANG Ying; MA Da-long (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the expression features of PDCD5 (programmed cell death 5 protein) in osteoarthritic and normal human cartilage, and speculate on its potential functions in the pathogenesis of osteoarthritis (OA). METHODS: Articular cartilage specimens were obtained from 30 patients with OA and 16 healthy patients at the time of arthroplasty. Expression of PDCD5 was detected by flow cytometry, immunofluorescence, RT-PCR and immunohistochemical analysis. RESULTS: Enhanced expression and nuclear accumulation of PDCD5 in OA chondrocytes were found. PDCD5-positive chondrocytes were mainly distributed in the superficial and deep zones of OA tissue sections, as opposed to, in the superficial and middle regions of normal healthy tissue sections. CONCLUSION: Since apoptotic chondrocyte death occurs more frequently in OA cartilage than in normal healthy cartilage and PDCD5 is an apoptosis-related protein, the different expression patterns of PDCD5 in OA cartilage from that in normal healthy cartilage indicate that PDCD5 is involved in the pathogenesis of OA.